Perkembangan Wisata Belanja “Oleh-Oleh Makanan” di Kota Malang - Sunaryo, Nonny Aji; Darma Putra, I Nyoman; Dewi, Made Heny Urmila (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 01, Juli 2019, 2019)
Shopping currently recognize as a tourism attraction. Malang is one of shopping tourism destinations in Indonesia, tourist go to Malang for bought food souvenirs. This study is aimed to find out the development of food souvenirs in Malang. This study uses a qualitative method. The results of this study indicate that the development of food shopping tourism has gone quickly within these past four years, starting from 2014 to 2018. This development is not only seen by the number of food souvenirs businesses, but also the variety of food souvenirs that are available in the market. There are 9 types of food souvenirs in Malang. Keywords: Shopping Tourism, Souvenirs, Food, Malang City